Rip1 (Receptor-interacting protein kinase 1) mediates necroptosis and contributes to renal ischemia/reperfusion injury - Linkermann, Andreas; Bräsen, Jan H.; Himmerkus, Nina; Liu, Shuya; Huber, Tobias B.; Kunzendorf, Ulrich; Krautwald, Stefan (Kidney international, 2012)
Loss of kidney function in renal ischemia/reperfusion injury is due to programmed cell death, but the contribution of necroptosis, a newly discovered form of programmed necrosis, has not been evaluated. Here, we identified the presence of death receptor–mediated but caspase-independent cell death in murine tubular cells and characterized it as necroptosis by the addition of necrostatin-1, a highly specific receptor-interacting protein kinase 1 inhibitor. The detection of receptor-interacting protein kinase 1 and 3 in whole-kidney lysates and freshly isolated murine proximal tubules led us to investigate the contribution of necroptosis in a mouse model of renal ischemia/reperfusion injury. Treatment with necrostatin-1 reduced organ damage and renal failure, even when administered after reperfusion, resulting in a significant survival benefit in a model of lethal renal ischemia/reperfusion injury. Unexpectedly, specific blockade of apoptosis by zVAD, a pan-caspase inhibitor, did not prevent the organ damage or the increase in urea and creatinine in vivo in renal ischemia/reperfusion injury. Thus, necroptosis is present and has functional relevance in the pathophysiological course of ischemic kidney injury and shows the predominance of necroptosis over apoptosis in this setting. Necrostatin-1 may have therapeutic potential to prevent and treat renal ischemia/reperfusion injury.